PRESENCIA DE EPIZOOS EN UN AMONOIDEO HETEROMORFO DEL MAASTRICHTIANO DE ARGENTINA: UNA INFERENCIA PALEOAUTOECOLOGICA (Ameghiniana, 2013)
Analysís of orientations of the bivalve Anomia d. solitaria Wilckens attached one specimen of Eubaculites ootacodensis (Stoliczka)indicates as most probable that the epizoans s ettled after the arnmonoid was dead and behaving as nekroplankton